2018
DOI: 10.1007/s10826-018-1180-7
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Families’ Perception of the Causes, First Manifestations, and Treatment of Autism Spectrum Disorder

Abstract: Compared to families from their host country, families from immigrant backgrounds who have a child with autism spectrum disorder (ASD) tend to experience greater difficulties in accessing, using, and complying with intervention services for their child. This disparity may be partially accounted for by cultural differences in how families perceive the causes and symptoms of ASD as well as their treatment priorities. The present study sought to document these perceptions in immigrant families living in a Canadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 58 publications
3
24
0
1
Order By: Relevance
“…On the other hand, the results suggest that other factors might also affect parents' prompt recognition of their child's atypical behavior indicative of ASD. For instance, the results point to gender differences in appraisal of the child's ASD symptoms, which is consistent with previous research with immigrant families in the multicultural contexts of Canada and the USA [25,84]. As our findings show, in some families from an immigrant background, mothers detected possible developmental problems in their children and applied various strategies to understand atypical behavior, while some fathers expressed denial or anger and were less accepting of their children's condition, despite being aware of autism or residing in Sweden for a long time.…”
Section: Parental Recognition Of Asd Symptom Onsetsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, the results suggest that other factors might also affect parents' prompt recognition of their child's atypical behavior indicative of ASD. For instance, the results point to gender differences in appraisal of the child's ASD symptoms, which is consistent with previous research with immigrant families in the multicultural contexts of Canada and the USA [25,84]. As our findings show, in some families from an immigrant background, mothers detected possible developmental problems in their children and applied various strategies to understand atypical behavior, while some fathers expressed denial or anger and were less accepting of their children's condition, despite being aware of autism or residing in Sweden for a long time.…”
Section: Parental Recognition Of Asd Symptom Onsetsupporting
confidence: 89%
“…To date, evidence from genetic studies on autism, including twin and family studies, shows that genetic factors can contribute to the development of ASD [89], and that ASD can overlap with other neurodevelopmental disorders sharing risk genes, resulting in the manifestation of signs and symptoms of autism in such syndromes as tuberous sclerosis, fragile X syndrome, and Rett syndrome [90]. The results demonstrate that almost half of the families (n = 7) could not say with certainty what exactly had caused autism in their children, which is consistent with the findings of a recent Canadian study conducted with immigrant families [25]. However, the results revealed that the majority of parents provided multiple explanations for their child's autism, which supports findings from previous studies [10,24,28].…”
Section: Parental Beliefs About the Causes Of Asdsupporting
confidence: 80%
See 1 more Smart Citation
“…There is also a scarcity of studies on the experiences of immigrant families with children with neurodevelopmental disorders in the healthcare system, and, to our knowledge, there is currently no systematic review available summarizing what is currently known about these families' interactions with providers or the utility of existing interventions. Nevertheless, the limited available evidence suggests that many barriers to detection, health care access, and treatment retention are similar across neurodevelopmental disorders and include structural/socioeconomic factors, such as underinsurance and service fragmentation, as well as social/cultural factors, such as lack of social support from the same-ethnic community and insufficient availability of culturally appropriate care (9,10,116,(118)(119)(120)(121)(122)(123)(124)(125)(126).…”
Section: Resultsmentioning
confidence: 99%
“…Potential barriers to diagnosis, access to and retention in specialized care reported in studies conducted among immigrants are similar across disorders and include both structural/socioeconomic factors (e.g., financial barriers, underinsurance, problems with transportation, fragmented services, and language barriers) and social/cultural factors (e.g., lack of social support, stigma and discrimination, insufficient understanding of the host country's health system, low health literacy, and differences in values and expectations between health service providers and parents) (9,10,116,(118)(119)(120)(121)(122)(123)(124)(125)(126).…”
Section: Barriers To the Detection Of Neurodevelopmental Disorders Hmentioning
confidence: 99%